Crianças quilombolas em um cineclube escolar: participação e protagonismo - Nogueira, Valdenise Lima Pimentel (2022)
This research proposed to analyze the relations of quilombola children with a School Film Club. Anchored in the nexus between education and cinema and situated in the field of Cultural Pedagogies, I established as a general objective: to analyze the relationship of quilombola children from the Escola Municipal José Albino Pimentel with the school Film Club. Frthis, I relied on different authors, located from the thematic axes, namely: quilombola children, Anete Abramowicz (2012; 2020), Wanderson Nascimento (2020); School film club, Inês Teixeira (2014; 2020), Débora Brutuce (2003); Participation, Diaz Bordenave (1983), Maria Gohn (2019); Protagonism, Adriana Friedmann (2017), Raquel Franzim (2017), among others. The methodological design is based on a qualitative study, carried out through a documentary, exploratory research. The data were produced through primary documents that were available in the collection of the José Albino Pimentel Kindergarten and Primary Municipal School, in Conde, Paraíba, the locus of the research. The main documents used were published audiovisual records, school reports about the Film Club, published articles about this experience, writings of the participating children about the school Film Club, alongside my notes in the field/memory notebook. In order to analyze the data, I used the content analysis, as presented by Laurence Bardin (2009). Based on this theoretical and methodological framework, it was possible to identify that children from the Gurugi and Ipiranga quilombos, Conde-PB, participated and played a leading role in the schoolls cineclubist activities. In this event, they revealed their way of being in the world, produced audiovisual content and shared their experiences with the seventh art.